Electronic Cigarettes: Harm Enhancement and Protection of Global Tobacco Interests - Glantz, Stanton A (Addicta: The Turkish Journal on Addictions, 2023)
Electronic cigarettes mimic cigarettes’ nicotine aerosol without burning tobacco. The assumption has been that electronic cigarettes are substantially safer than cigarettes because they avoid combustion. This assumption, combined with assumptions that electronic cigarettes are effective for cigarette cessation and do not appeal to youth, led many to argue electronic cigarettes are harm reduction. By 2023, evidence revealed higher risks than assumed, that electronic cigarettes as consumer products do not help smokers quit, and that electronic cigarettes have addicted millions of youth to nicotine. Dual use (using both electronic cigarettes and cigarettes) is more harmful than just smoking cigarettes. The failure of electronic cigarettes as consumer products to help people stop smoking makes their relative toxicity compared to cigarettes a moot point. Electronic cigarettes have also played a role in the multinational tobacco companies’ efforts to reposition themselves as socially responsible, which helps protect their financial and political interests. Countries, including Turkey, that have prohibited the import and avoided the sale of electronic cigarettes have done better overall at controlling the electronic cigarette epidemic than countries, including the United States and England, that have adopted more laissez-faire policies toward electronic cigarettes. Turkey should maintain and ensure effective enforcement of its current policies to continue to protect its population from electronic cigarettes.
Keywords: E-cigarettes; electronic cigarettes; smoking cessation; youth; dual use; tobacco industry